y+10=-(x-15)

Simple and best practice solution for y+10=-(x-15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+10=-(x-15) equation:


Simplifying
y + 10 = -1(x + -15)

Reorder the terms:
10 + y = -1(x + -15)

Reorder the terms:
10 + y = -1(-15 + x)
10 + y = (-15 * -1 + x * -1)
10 + y = (15 + -1x)

Solving
10 + y = 15 + -1x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + y = 15 + -10 + -1x

Combine like terms: 10 + -10 = 0
0 + y = 15 + -10 + -1x
y = 15 + -10 + -1x

Combine like terms: 15 + -10 = 5
y = 5 + -1x

Simplifying
y = 5 + -1x

See similar equations:

| 5u+2v-2(4u-5v)= | | .75(.25x+8)-(25x+2)=0.375(4-x)-.25x | | X/19=5/95 | | -6y-12=-18y-23 | | 6x-12=x-22 | | y-2=3(x+1) | | 15/45=x/12 | | x^2-20x-98=0 | | 9b+4=2b+46 | | 25r^3-16r=0 | | 25r^3-16r=0 | | 11-8x=7x+17 | | 139-5x=3x-19 | | 2(x+6)=3(x-4)+5 | | q-7/4=3 | | v/11=5/3 | | -42-2x=6-6x | | 7-9x=7x+18 | | (7x^3+4x)(x^2+2)= | | 4(x-3)=23-x | | 9(2+x)=63 | | 4x+13=94 | | 2(3-5+7)+6= | | 5(14-x)=60 | | 8(x+1)=48 | | 3x(3+5)=24 | | -32=4(x+3) | | (2x+4y)+(4x+7y)=180 | | -3x^2+21x=15 | | 5x+5+4x+5+35=180 | | 1=-.5(3k-4) | | 3.50x=84 |

Equations solver categories